Natural Course of Allergic and Nonallergic Rhinitis After 2 Years in Korean Children - Seung-Hoon Lee; Ji Ho Choi; Jeffrey D. Suh; Sochung Chung; Seok-Chan Hong; Jin Kook Kim; Jae Hoon Cho (Clinical and Experimental Otorhinolaryngology, 2016)
Objectives. Allergic and nonallergic rhinitis are very common disease for children, however, little is known about their natural courses in the general population. The purpose is to evaluate the natural course of allergic and nonallergic rhinitis in children. Methods. We analyzed data from Snoring Child Cohort of 178 children (107 boys and 71 girls). All children entered the study at the age of 7 years (range, 6.5 to 7.4 years). Questionnaires regarding chronic rhinitis, a skin prick test (SPT) for 5 inhalent allergens, and specific IgE for 2 dust mites were administered. Children were classified into 4 groups: allergic rhinitis (rhinitis, positive SPT), nonallergic rhinitis (rhinitis, negative SPT), sensitization only (no rhinitis, positive SPT), and control (no rhinitis, negative SPT). We repeated follow them annually, and analyzed the data of first and third year for this study. Results. Finally, the data of 122 children were analyzed. Among 18 children with allergic rhinitis at 7 years, 13 (72%) became sensitization only after 2 years and 5 (28%) were remained having allergic rhinitis. Five out of 19 children (26%) with nonallergic rhinitis developed into allergic rhinitis and 7 (37%) into control at 9 years. Twenty-four out of 28 children (86%) with sensitization only at 7 years remained the same at 9 years. Among 57 control children at 7 years, 2 (4%) developed into allergic rhinitis, 7 (12%) with nonallergic rhinitis, and 16 (28%) with sensitization only at 9 years. Conclusion. The status of chronic rhinitis and allergen sensitization is ever-changing in children.